1989
DOI: 10.1097/00006123-198911000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic pulmonary edema in the acute stage of hemorrhagic cerebrovascular disease

Abstract: Extravascular lung water (EVLW) was measured by the double-indicator dilution method in 25 patients with hemorrhagic cerebrovascular diseases. EVLW had a significantly positive correlation with both alveolar-arterial oxygen difference (AaDO2) and intrapulmonary shunt. The value of EVLW in the acute stage in 15 patients with increased AaDO2 more than 20 mm Hg was 7.8 +/- 2.2 ml/kg and that in the chronic stage 4 weeks after onset significantly decreased to 4.6 +/- 0.7 ml/kg (P less than 0.001). The value of EVL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Measurement of various parameters in patients with different cerebrovascular disease using a Swan-Ganz catheter and the double-indicator dilution method found that patients with neurogenic pulmonary edema showed no fluctuations in hemodynamic parameters, and only EVLWI was elevated. 25) The theory of the ITBVI measurement method is basically the same as that of the PiCCO system used by us, and the results are very similar.…”
Section: Discussionmentioning
confidence: 74%
“…Measurement of various parameters in patients with different cerebrovascular disease using a Swan-Ganz catheter and the double-indicator dilution method found that patients with neurogenic pulmonary edema showed no fluctuations in hemodynamic parameters, and only EVLWI was elevated. 25) The theory of the ITBVI measurement method is basically the same as that of the PiCCO system used by us, and the results are very similar.…”
Section: Discussionmentioning
confidence: 74%
“…However, in a small sample-size retrospective study, there was no evidence for high-permeability edema or cardiac failure in half of patients who presented with oxygenation disturbances. In those patients, pulmonary edema may be due to extravascular lung water [90], because the latter was significantly and positively correlated with impaired oxygenation in a study of patients with hemorrhagic stroke [91]. Thirdly, some molecules, such as S100B, E-selectin, and caspase-1, can be the link between the brain and the lung that determine the development of NPE after SAH.…”
Section: Manifestations Of Nonneurologic Complications After Sahmentioning
confidence: 99%
“…Initial studies suggested that the development of NPE in patients with TBI [26] and hemorrhagic stroke wash more frequent in those patients who had higher intracranial pressures (ICP) and low cerebral perfusion pressures (CPP, mean arterial pressure (MAP-ICP) [27]. The importance of these landmark studies is that the development of NPE occurred in the absence of clear lung injury and normal chest X-ray (CXR) on admission, suggesting that brain injury was a risk factor for this phenomenon.…”
Section: Ali and Ardsmentioning
confidence: 99%